APOE ɛ2 is associated with white matter hyperintensity volume in CADASIL. Issue 1 (January 2016) - Gesierich, Benno; Opherk, Christian; Rosand, Jonathan; Gonik, Mariya; Malik, Rainer; Jouvent, Eric; Hervé, Dominique; Adib-Samii, Poneh; Bevan, Steve; Pianese, Luigi; Silvestri, Serena; Dotti, Maria T; et al.
Apolipoprotein E ( APOE ) increases the risk for Alzheimer's disease ( ɛ 4 allele) and cerebral amyloid angiopathy ( ɛ 2 and ɛ 4), but its role in small vessel disease (SVD) is debated. Here we studied the effects of APOE on white matter hyperintensity volume (WMHV) in CADASIL (cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy), a nonamyloidogenic angiopathy and inherited early-onset form of pure SVD. Four hundred and eighty-eight subjects were recruited through a multicenter consortium. Compared with APOE ɛ 3/ ɛ 3, WMHV was increased in APOE ɛ 2 ( P = 0.02) but not APOE ɛ 4. The results remained significant when controlled for genome-wide genetic background variation. Our findings suggest a modifying influence of APOE ɛ 2 on WMHV caused by pure SVD.